Sosialisasi Perangkat Pembelajaran Matematika Meteri Bangun Datar Berbasis CRT - Yulia Ruti Cahyanti; Fauziyyah Muna Karomah; Dina Celline Megasari; Putri Zudhah Ferryka (CV. ITTC INDONESIA, 2024)
The program to increase understanding of elementary school level concepts is carried out in the form of activities to socialize understanding of the implementation of the Culturally Responsive Teaching (CRT) approach. The aim of this activity is to provide knowledge and understanding for prospective elementary school teachers in improving their competence, especially understanding the implementation of CRT. This socialization activity uses lecture, question and answer and discussion methods. The training participants were 23 elementary school teachers. Prospective elementary school teachers can understand and comprehend the material provided in this activity, because this material is equipped with examples of CRT approach teaching modules, so that teachers' obstacles in implementing CRT in schools can be overcome in the teaching process.